2018
DOI: 10.1029/2018wr023078
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Turbulence on Hyporheic Exchange and Local‐to‐Global Nutrient Processing in Streams

Abstract: New experimental techniques are allowing, for the first time, direct visualization of mass and momentum transport across the sediment‐water interface in streams. These experimental insights are catalyzing a renaissance in our understanding of the role stream turbulence plays in a host of critical ecosystem services, including nutrient cycling. In this commentary, we briefly review the nature of stream turbulence and its role in hyporheic exchange and nutrient cycling in streams. A simple process‐based model, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 57 publications
3
50
0
Order By: Relevance
“…Thus, investigation of the macroinvertebrate community response to aquatic ecosystems has been a hotspot [4]. The hyporheic zone (HZ), which is the volume of riverbed sediments where surface water (SW) and groundwater (GW) are mixing [5,6], is a storage zone in river ecosystems for transported and released solutes [1,7,8]. Many ecological processes are related to hyporheic exchange, because this affects the substrate properties and water quality and produces physicochemical gradients to which macroinvertebrates are sensitive [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigation of the macroinvertebrate community response to aquatic ecosystems has been a hotspot [4]. The hyporheic zone (HZ), which is the volume of riverbed sediments where surface water (SW) and groundwater (GW) are mixing [5,6], is a storage zone in river ecosystems for transported and released solutes [1,7,8]. Many ecological processes are related to hyporheic exchange, because this affects the substrate properties and water quality and produces physicochemical gradients to which macroinvertebrates are sensitive [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial momentum coupling modifies the flow structure across the surface-subsurface continuum by increasing subsurface velocities and amplifying turbulent shear and vertical stresses near the SWI (Voermans et al, 2017). The resulting interfacial exchange rates can increase by orders of magnitude beyond advective pumping (Grant, Gomez-Velez, & Ghisalberti, 2018;O'Connor & Harvey, 2008). Turbulent energy diminishes exponentially with depth in the streambed, typically limiting the thickness of the turbulent interfacial layer to the order of several grain diameters (Breugem et al, 2006;Manes et al, 2009;Vollmer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This parameterization is consistent with experimental results for turbulent flows over flat porous beds (Chandler et al, ), and with the exponential attenuation of the pumping‐induced seepage velocity in case of bed form induced hyporheic exchange (Bottacin‐Busolin & Marion, ; Elliott & Brooks, ). (Grant et al, ) used a depth‐invariant effective diffusivity to represent the vertical mass transfer across the stream‐water interface and found that, on average, the effective diffusivity for beds with bed forms and riffle‐pool sequences is about 3.5 times higher than that predicted for flat sediment beds. This can be regarded as a small increase in comparison to the six‐decade variability in the effective diffusivity associated with changes in the bed permeability and shear velocity (Grant et al, ).…”
Section: Resultsmentioning
confidence: 99%